Measurement Model Value Aspects Of Teacher Leadership In Vocational Education - Mohammad, Nazeri (Sebelas Maret University, 2016)
Teaching profession at present is very challenging and the teachers themselves must be prepared to deal with it. The issue of teachers and the teaching profession continue to gain attention and often widely debated whether in the media, among the general public and even discussed until the national level. Negative sentiment against teachers often receives media attention although not authentic, and it creates a feeling of prejudice and less happy society on the individual teacher. These issues need to be addressed wisely by all teachers and the parties involved so that the dignity of the profession remain respected. Teachers need to show good values of the students, school and community. This is important because there is value in teachers will influence others to stay in school or otherwise. People often look at the behavior of teachers and assess externally only. Teachers must have admirable traits that can guide and educate students to become excellent once formed their personal character. This study aimed to verify the instrument model aspects of the leadership of teachers in technical and vocational education. Specifically, the objectives of this study were to confirm the scale of the measurement model teacher leadership and to identify the reliability of the instrument model. This study used a questionnaire to collect data from respondents. The questionnaire used is divided into two parts, Part A and Part B Section A consisted of demographic data, while Part B contains 53 item questionnaire measuring aspects of the leadership of the teachers in improving teaching and student learning, teacher leadership skills in improve relations and cooperation with the community and other parties, leadership skills and attributes of teachers in skill lead. And practice leadership skills teacher professional learning for continuous improvement. The study population consisted of all students of semester 8, IPG Zone east coast of peninsular Malaysia. This study used a sample of all the population to study. However, only 153 questionnaires that can be used for analysis and the respondents for this survey. This questionnaire has been validated by a panel of experts consisting of a lecturer who specializes in the study in IPGK Zone east coast of Malaysia, to get the validity of the content. The questionnaire was constructed and tested for suitability in the context of teacher education in IPGK Zone east coast of Malaysia.